PENGARUH PUPUK ORGANIK DAN JUMLAH BIJI PER LUBANG TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays Var. Saccharata Sturt) - Winda Kinanti T.P,; Retno Tri Purnamasari (Universitas Tribhuwana Tunggadewi, 2022)
This study aimed to determine the effect of the dosage of organic fertilizer and the number of seeds in the planting hole on the growth and yield of sweet corn. The research was designed in a factorial randomized block design. Treatments tested used fertilization dose (P) consisting of three levels, namely dose of organic fertilizer 1.5 tons ha-1 (P1), the dose of organic fertilizer 2 tons ha-1 (P2), and the dose of organic fertilizer 2.5 tons ha-1 (P3). The other factor used several seeds in hole-1 (J) consisting of three levels, i.e. one seed of plant hole-1 (J1), two seeds on plant hole-1 (J2), and three seeds on plant hole-1 (J3) each combination repeated three times. The results showed that a combination of organic fertilizer 2.5 ton ha-1 with three seed planting hole-1 significantly increased in growth and yield of sweet corn.